Gender Justice Principles in the Islamic Inheritance System - Ahmad Sholikhin Ruslie; Rahadyan Widarsadhika Wisnumurti; Dedy Muharman (Mimbar Keadilan, 2024)
This study aims to examine the principles of gender justice within the Islamic inheritance system, based on Surah An-Nisa’ verses 11-12, which stipulate a 2:1 ratio (a male receives two shares of the inheritance compared to a female). However, in the modern era, with changing times and human mindsets, as well as demands for equal rights, this 2:1 stipulation is considered a problem of justice. This research is normative juridical research, employing the library research method. The legal materials used include literature studies, such as interpretations of sacred texts, fiqh books, books, journals, previous research results, websites, and other writings related to the issues being studied. The results of this research indicate that justice refers to fair and equal treatment for every individual in accordance with the principles of the Qur'an and Hadith. However, in the context of Islamic inheritance distribution, challenges arise due to social and cultural changes that affect its interpretation and application. Although the principles of justice remain, there needs to be a renewal in the interpretation and implementation of Islamic law to reflect social and economic developments and to advocate for gender equality. This adaptation is not an effort to oppose culture or religion but a step towards a more just society for all individuals, regardless of gender. In making this adaptation, religious values and cultural traditions must be reinterpreted in accordance with the spirit of inclusivity and justice inherent in Islam, so that Islam remains a relevant moral and legal guide for its followers.